إدارة الأزمات من منظور السياسة الشرعية - Taghreed Yaaqub Abu Sbaih (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
The concept of crisis management has become one common terminology in various fields, especially in shariah science. This study, the presentation of this confrontation and how it confronts a global disease crisis known as the Corona